2015
DOI: 10.5897/ijnam2014.0174
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anthropometry in rural and urban areas of Ogun-East senatorial district, Nigeria: A comparative study

Abstract: Maternal nutrition is a well documented determinant of pregnancy outcome. Maternal anthropometry has been shown to be a predictor of the occurrence or otherwise of low birth weight, foetal macrosomia, increased maternal and newborn morbidity and mortality. Rural-urban differences in nutritional status have been documented in literature. A cross-sectional comparative study of the anthropometric indices of 720 pregnant women accessing antenatal care at selected rural and urban primary health centres in Ogun Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
5
2
Order By: Relevance
“…10 The mean maternal pre pregnancy BMI of the study population was 24.10±5.4 kg/m 2 which was much lower than a value of 27.9±4.3 kg/m 2 found by a study conducted in Nigeria but nearer to a value of 24±4.3 kg/m 2 determined by a study conducted in Norway. 11,12 Our study found no significant correlation of maternal haemoglobin level with developmental outcomes of the infant, similar to a study conducted in Sri Lanka. 13 Contrary to some previous literature our study showed a positive correlation between BMI and PI.…”
Section: Resultssupporting
confidence: 86%
“…10 The mean maternal pre pregnancy BMI of the study population was 24.10±5.4 kg/m 2 which was much lower than a value of 27.9±4.3 kg/m 2 found by a study conducted in Nigeria but nearer to a value of 24±4.3 kg/m 2 determined by a study conducted in Norway. 11,12 Our study found no significant correlation of maternal haemoglobin level with developmental outcomes of the infant, similar to a study conducted in Sri Lanka. 13 Contrary to some previous literature our study showed a positive correlation between BMI and PI.…”
Section: Resultssupporting
confidence: 86%
“…The mean maternal pre pregnancy BMI in the study population was 19.74 ± 2.36. which was much lower than that found by Jeminusi et al[12] (27.9 ± 4.3 kg/m 2 ) and Koepp et al[13] (24 ± 4.3 kg/m 2 ) but nearer to an Indian study conducted by Kader et al[14] (21.3 ± 4.5 kg/m 2 ). The mean pre-pregnancy Body Mass index was found to be 19.25 ± 1.68 kg/m 2 in LBW group and 19.98 ± 2.60 kg/m 2 in normal birth weight group (difference is statistically significant z=3.75, p=0.001).…”
contrasting
confidence: 53%
“…[ 28 29 ] Mid-upper arm circumference was assessed using the measuring tape in centimeters (cm) and classified as normal (for readings above 23 cm), mild to moderate malnutrition (for reading between 21 and 23 cm) and severe malnutrition (for readings below 21 cm), as documented in literature. [ 30 31 ] Data collected daily were checked for completeness and accuracy, before entry. Data analysis was carried out, using SPSS (Statistical Package for the Social Sciences) version 17 (SPSS Inc.…”
Section: Methodsmentioning
confidence: 99%